2022
DOI: 10.1093/infdis/jiac272
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and Breadth of the Neutralizing Antibody Response to a Live-Attenuated Tetravalent Dengue Vaccine

Abstract: An effective dengue vaccine should ideally induce broadly neutralizing antibody (nAb) responses against all four dengue virus (DENV) serotypes. We characterized the specificity and breadth of the nAb response to TAK-003, a live attenuated tetravalent dengue vaccine, in serum samples from phase 2 and 3 clinical trials. Microneutralization tests using post-vaccination serum showed comparable neutralization against diverse DENV-1−4 genotypes. Reporter virus particle neutralization assays post- depletion of anti-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…TAK-003 has been shown to effectively prevent virologically confirmed dengue cases and hospitalization caused by any DENV serotype [ 10 , 11 ]. Immune responses elicited by TAK-003 include broad cellular responses (B and T cells), and humoral immunity targeting all 4 DENV serotypes and multiple viral antigens [ 14–17 ], including type-specific and cross-reactive nAbs [ 20 ]. Complement deposition mediated by antibodies elicited by DENV infection has been shown to contribute to prevention of subsequent symptomatic DENV3 infection by facilitating C1q-dependent virolysis and destruction of infected cells [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TAK-003 has been shown to effectively prevent virologically confirmed dengue cases and hospitalization caused by any DENV serotype [ 10 , 11 ]. Immune responses elicited by TAK-003 include broad cellular responses (B and T cells), and humoral immunity targeting all 4 DENV serotypes and multiple viral antigens [ 14–17 ], including type-specific and cross-reactive nAbs [ 20 ]. Complement deposition mediated by antibodies elicited by DENV infection has been shown to contribute to prevention of subsequent symptomatic DENV3 infection by facilitating C1q-dependent virolysis and destruction of infected cells [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immune responses elicited by TAK-003 target the viral structural and nonstructural (NS) proteins [ 14–17 ], leading to expression of innate immune genes associated with protective vaccine-associated responses [ 18 ], as well as activation of interserotype cross-reactive T cells (helper and cytotoxic [ 16 , 17 ]) and memory B cells [ 14 ]. Vaccination also elicits production of type-specific and cross-reactive neutralizing antibodies (nAbs) [ 10 , 19 , 20 ], and NS1-binding and highly mature virus-binding immunoglobulin G (IgG) [ 15 , 21 ].…”
mentioning
confidence: 99%
“…Sequential infections with two different DENV types appears to impart a mix of broadly protective homo-and heterotypic immunity, as evidenced by the very rare occurrence of clinically relevant third and fourth DENV infections 75 . Vaccine developers must pursue the development of tetravalent vaccine formulations containing antigens to each DENV type, but it has been difficult, especially with replicating vaccines, to avoid some element of immunodominance and an imbalance of homotypic immunity to the dominant DENV type and cross-reactive immunity to the others [76][77][78][79][80][81][82] . As a result, a major lesson learned when assessing dengue vaccine performance is that immunogenicity does not necessarily translate into clinical efficacy.…”
Section: Immunogenicity Does Not Guarantee Efficacymentioning
confidence: 99%
“…Reporter virus particle neutralization assays post depletion of anti-DENV-2 nAbs demonstrated that the nAb response to DENV-1, DENV-3, and DENV-4 constitutes both type-specific and cross-reactive nAbs. Therefore, TAK-003 induces broad tetravalent type-specific and cross-reactive nAb responses [63].…”
Section: Tetravalent Live-attenuated Recombinant Dengue Vaccine Candi...mentioning
confidence: 99%